Successful treatment of suckling Red Angus calves for bovine respiratory disease is not associated with increased mean pulmonary arterial pressures at weaning. (12th May 2018) - Neary, Joseph M; Church, Dee; Reeves, Nathan; Rathmann, Ryan J
Abstract: The purposes of this study were to determine if the successful treatment of bovine respiratory disease (BRD ) in suckling calves was associated with a long-term increase in mean pulmonary arterial pressure (mPAP ) and, to screen for associations between blood leukogram variables and mPAP. A cohort of Red Angus calves ( n = 74) were followed from birth to weaning at an altitude of 975 m. Calves were weaned at 172 ± 14 d when their mPAP was measured and whole blood collected. Thirty calves that had been treated for BRD (34 to 45 d prior) and 30 calves that had not required treatment for BRD were sampled. Treatment for BRD had no effect on mPAP ( P = 0.37). Mean mPAP was 48 ± 8 mm Hg (± SD) with a minimum of 34 mm Hg and a maximum at 69 mm Hg. Weaning weight and sex tended to be associated with mPAP, but they explained just 5% of the variation in mPAP ( P = 0.08; Adj. r 2 = 0.05). Fibrinogen ( P = 0.008) and absolute lymphocyte count ( P = 0.06) were negatively associated with mPAP, whereas absolute monocyte count was positively associated with mPAP ( P = 0.01). The findings of this study suggest that pre-weaning treatment for BRD does not increase a calves' post-weaning risk of congestive right heart failure. Further, components of the immune and acute phase response system may play a role in the development and progression of pulmonary hypertension.